The story of Oklahoma - Baird, W. David; Goble, Danney (University of Oklahoma Press, 2013)
Written by award-winning Oklahoma authors -- Chapter and unit reviews revised to meet 2012 Process and Literacy Skills Standards -- Questions and activities that help develop students’ Common Core social studies reading and writing literacy skill -- Review and essay questions for conceptual understanding and problem-solving -- Introductions with learning objectives for each unit and chapter -- Timelines for key Oklahoma and national events -- Primary sources throughout the text -- Balanced treatment of race, ethnicity, class, and religion -- Integrated vocabulary to enhance reading skills, activities that encourage student participation -- Sidebars that highlight key concepts and historical developments